ChemInform Abstract: Metal‐Free One‐Pot Synthesis of Amides Using Graphene Oxide as an Efficient Catalyst. Issue 12 (March 2015) - Kumari, Shweta; Shekhar, Amiya; Mungse, Harshal P.; Khatri, Om P.; Pathak, Devendra D.
Abstract The method for the title synthesis needs no transition metal catalysts and proceeds in shorter reaction time.